Screenertia: Understanding "Stickiness" of Media Through Temporal Changes in Screen Use. (July 2023) - Brinberg, Miriam; Ram, Nilam; Wang, Jinping; Sundar, S. Shyam; Cummings, James J.; Yeykelis, Leo; Reeves, Byron
Descriptions of moment-by-moment changes in attention contribute critical elements to theory and practice about how people process media. We introduce a new concept called screenertia and use new screen-capture methodology to empirically evaluate its occurrence. We unobtrusively obtained 400, 000+ screenshots of 30 participants' laptop screens every 5 seconds for 4 days to examine individuals' attention to their screens and how the distribution of attention differs across media content. All individuals' screen segments were best described by a log-normal survival function—evidence of screenertia. Consistent with the literature on uses and gratifications of media, news/entertainment activities were the most "sticky." These findings indicate that screenertia is not only related to the level of interactivity of media content but is also related to its modality and agency. Discussion of the findings highlights the importance of theorizing, examining, and modeling the specific time scales at which media behaviors manifest and evolve.